A randomized trial comparing 4.8 vs. 2.4 g/day of oral mesalazine for maintenance of remission in ulcerative colitis. Issue 11 (November 2015) - Pica, Roberta; Cassieri, Claudio; Cocco, Andrea; Zippi, Maddalena; Marcheggiano, Adriana; De Nitto, Daniela; Avallone, Eleonora Veronica; Crispino, Pietro; Occhigrossi, Giuseppe; Paoluzi, Paolo
Abstract Background Mesalazine is used as maintenance therapy in ulcerative colitis but the optimal dosage is still controversial. Aim To compare the remission-maintenance efficacy and tolerability of two daily doses of oral mesalazine (4.8 g and 2.4 g) in patients with ulcerative colitis with frequent relapses in a randomized controlled trial. Methods 112 ulcerative colitis patients in remission were enrolled and randomly allocated to treatment for 1 year with oral mesalazine at a daily dose of 4.8 g (n = 56, Group A) or 2.4 g (n = 56, Group B). Results At the end of the 12 months, intention to treat analysis revealed persistent remission in 42 (75%) in Group A and 36 (64.2%) in Group B (p = 0.3). The higher daily dose (4.8 g) proved to be significantly more effective for maintaining remission in patients under 40 years of age (90.5% Group A vs. 50% Group B; Fisher's exact test, p = 0.0095) and in those with extensive disease (90.9% Group A vs. 46.7% Group B; Fisher's exact test, p = 0.0064). Conclusions In ulcerative colitis patients younger than 40 years and/or with extensive disease, a daily dose of 4.8 g oral mesalazine results in increased rates and duration of remission compared to 2.4 g.